Solutions to a multi-phase model of sea ice growth - Tang Yangxin; Zheng Lin; Luan Liping (Open Mathematics, 2021)
The multi-phase systems have found their applications in many fields. We shall apply this approach to investigate the multi-phase dynamics of sea ice growth. In this paper, the weak solution existence and uniqueness of parabolic differential equations are proved. Then large-time behavior of solutions is studied, and also the existence of the global attractor is proved. The key tool in this article is the energy method. Our existence proof is only in one dimension.